Clinical, diagnostic, and follow-up characteristics of children with ectopic thyroid: An 11-year tertiary referral center experience - Fouzea Mol Saidalikutty; Raghupathy Palany; Narasimhan Anirudhan; Ayyavoo Ahila (Indian Journal of Child Health, 2021)
Background: Information on the clinical data and follow-up of ectopic thyroid (ET) in pediatric population in India is scanty; hence, this study aims to add more information on this entity. Objective: This study was undertaken to analyze the clinical, biochemical characteristics, and scintigraphy findings at diagnosis and follow-up response to thyroxine (T4) replacement in children with ET. Methods: This study was conducted at the Paediatric Endocrinology Department of Tertiary Center from January 2005 to March 2016. In children with abnormal thyroid function, scintigraphy was done before T4 replacement to establish the diagnosis of permanent congenital hypothyroidism. Thyroid dose modification, growth monitoring was done on follow-up. In infants and children without an etiological diagnosis, at ?3 years of age, thyroid function test, scintigraphy was done after stopping treatment for 4 weeks. The initial clinical, biochemical parameters, follow-up data were analyzed. Results: Among 54 children with ET, 39 (72.2%) were girls. The mean age of presentation was 3.3 years and the average age at diagnosis on the basis of presentation with isolated short stature was 7.3 years. Developmental delay was the predominant symptom (24.9%) in children between age 1 month and 5 years. Among them, 78.5% had initial thyroid-stimulating hormone (TSH) >60 mIU/ml. During the first follow-up visit, high TSH >10 mIU/ml and >60 mIU/ml with normal levels of T4 were found in 29.6% and 7.4%, respectively, who were treatment compliant. TSH levels regressed gradually in the subsequent visits without any increase in T4 dose. Neck masses and externally visible lingual thyroids regressed with oral T4 without any surgical intervention. Conclusions: The assessment of adequacy of T4 replacement at follow-up needs both TSH and T4 levels. The prompt identification, early, and adequate treatment of children with ET can prevent possible surgical intervention.